Enhancing low-grade waste heat recovery by lead-free ferroelectric Ba(Zr0.1Ti0.9)O3 with Sr and Ca isovalent dopants. Issue 10 (15th May 2023) - Ngo, Nguyen Chi Trung; Sugiyama, Hironari; Sodige, Buddhika Amila Kumara; Wiff, Juan Paulo; Furuno, Hideto; Yamanaka, Satoru; Kim, Yoonho; Suzuki, Tsuneo; Baba, Masaaki; Takeda, Masatoshi; Yamada, Noboru; Niihara, Koichi; et al.
Abstract: Kim's novel electrothermodynamic cycle enables the Ba(Zr0.1 Ti0.9 )O3 ceramic to achieve a significantly high energy density at temperatures 20–120 °C by utilizing its mixed ferroelectric-relaxor behavior. This allows the material to replace lead-based compositions and provides a clean, environmentally friendly, sustainable power source from low-grade waste heat for technologies like the Internet of Things. However, this still does not represent the highest potential of this material. In this research, our group utilizes the smaller ionic radii of the isovalent dopants Sr and Ca to enhance the relaxor behavior, hence improving the pyroelectric conversion ability of Ba(Zr0.1 Ti0.9 )O3 . Actual measurements using the Olsen and Kim cycles revealed enhancement by factors of 1.29 and 1.55 for each cycle due to the improvement in remanent and saturated polarization and temperature dependence of the pyroelectricity. The results suggested that lead-free Ba(Zr0.1 Ti0.9 )O3 has promising potential as a critical pyroelectric waste heat recovery-based element.